Analysis of Upstream Cloud Technology Acceptance at Pertamina Hulu Energi Regional 4 - Fatahillah, Ahmad Dzikra; Noviaristanti, Siska; Awaluddin, Muhammad (Eastasouth Institute, 2025)
This study aims to analyze the factors influencing the acceptance of Upstream Cloud technology at PT Pertamina Hulu Energi Regional 4. Upstream Cloud is part of the company's digital transformation strategy, expected to improve operational efficiency and competitiveness in the oil and gas industry. Using the Technology Acceptance Model (TAM) approach, this research examines the influence of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Confidence Level of Users (CL), and Cost Effectiveness (CE) on the level of technology acceptance within the organization. The research was conducted through a survey involving employees of PT Pertamina Hulu Energi Regional 4, with data analyzed using inferential statistical methods to determine the relationships and the magnitude of influence of each variable. The results indicate that PU has a positive and significant effect of 33.3%, PEOU of 9.2%, CL of 39.1%, and CE of 14.9% on technology acceptance. Simultaneously, these four variables contribute a total of 96.5% to the acceptance of Upstream Cloud technology. These findings have important strategic implications for the company, including the need to enhance user competence and confidence through technical training and mentoring, intensify communication regarding the tangible benefits of cloud technology, and strengthen technical support. Additionally, although PEOU has a relatively small influence, ensuring ease of use remains essential to minimize adoption barriers, particularly for non-technical users. Regular evaluations of the technology's effectiveness are also recommended to adapt to the dynamic operational needs and technological advancements in the oil and gas industry.